2015
DOI: 10.1016/j.geoderma.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Linking satellite derived LAI patterns with subsoil heterogeneity using large-scale ground-based electromagnetic induction measurements

Abstract: This version available http://nora.nerc.ac.uk/510335/ NERC has developed NORA to enable users to access research outputs wholly or partially funded by NERC. Copyright and other rights for material on this site are retained by the rights owners. Users should read the terms and conditions of use of this material at http://nora.nerc.ac.uk/policies.html#access NOTICE: this is the author's version of a work that was accepted for publication in Geoderma. Changes resulting from the publishing process, such as peer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 56 publications
2
100
0
Order By: Relevance
“…Using more precise and high resolution estimates of remotely sensed LAI in hydrological and radiative transfer models may improve soil moisture [85] and evapotranspiration retrieval [86]. Remotely sensed fine resolution LAI maps identify the field scale variability of vegetation and it could be used to identify the subsoil heterogeneity in addition to geophysical methods [59]. Moreover, the analysis of the red-edge spectral band impact to LAI estimation provides basic information also for the upcoming Sentinel-2 mission [87].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using more precise and high resolution estimates of remotely sensed LAI in hydrological and radiative transfer models may improve soil moisture [85] and evapotranspiration retrieval [86]. Remotely sensed fine resolution LAI maps identify the field scale variability of vegetation and it could be used to identify the subsoil heterogeneity in addition to geophysical methods [59]. Moreover, the analysis of the red-edge spectral band impact to LAI estimation provides basic information also for the upcoming Sentinel-2 mission [87].…”
Section: Discussionmentioning
confidence: 99%
“…The area is covered with Quaternary sediments, mostly fluvial deposits from the Rhine/Maas River and the Rur river system [59]. They form the underlying sediments, whereas floodplain sediments belong to Pleistocene and Holocene sediments.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitation is continuously monitored at 5-min intervals by the twin dual-polarized X-band Doppler radars BoXPol in Bonn and JuXPol in Jülich on the Sophienhöhe (e.g., Ryzhkov et al 2014), a hill created from open-cast mining and jutting roughly 200 m out of the surrounding terrain. 2; for details, see von Hebel et al (2014) and Rudolph et al (2015)] showed a clear link between subsoil patterns of higher clay content originating from paleorivers (red dashed lines in Fig. The area is also covered by four C-band radars of DWD, which have been recently catchment (see Fig.…”
Section: Monitoring Of the Rur Catchmentmentioning
confidence: 93%
“…In accordance with these local hydrogeological and climatic differences, land use and vegetation is clearly distinguishable: Forest and grassland characterize the south, whereas in the north fertile agricultural land predominates [76][77][78]. Soils can be locally very heterogeneous due to their origin in floodplain deposits and loess [79]. The Rur catchment is part of the Terrestrial Environmental Observatories (TERENO) network [80,81].…”
Section: Tereno Site Rur Catchmentmentioning
confidence: 98%